Impact of MET inhibition on small‐cell lung cancer cells showing aberrant activation of the hepatocyte growth factor/MET pathway. Issue 7 (8th June 2017) - Taniguchi, Hirokazu; Yamada, Tadaaki; Takeuchi, Shinji; Arai, Sachiko; Fukuda, Koji; Sakamoto, Shuichi; Kawada, Manabu; Yamaguchi, Hiroyuki; Mukae, Hiroshi; Yano, Seiji
Abstract : Small‐cell lung cancer (SCLC) accounts for approximately 15% of all lung cancers, and is characterized as extremely aggressive, often displaying rapid tumor growth and multiple organ metastases. In addition, the clinical outcome of SCLC patients is poor due to early relapse and acquired resistance to standard chemotherapy treatments. Hence, novel therapeutic strategies for the treatment of SCLC are urgently required. Accordingly, several molecular targeted therapies were evaluated in SCLC; however, they failed to improve the clinical outcome. The receptor tyrosine kinase MET is a receptor for hepatocyte growth factor (HGF), and aberrant activation of HGF/MET signaling is known as one of the crucial mechanisms enabling cancer progression and invasion. Here, we found that the HGF/MET signaling was aberrantly activated in chemoresistant or chemorelapsed SCLC cell lines (SBC‐5, DMS273, and DMS273‐G3H) by the secretion of HGF and/or MET copy number gain. A cell‐based in vitro assay revealed that HGF/MET inhibition, induced either by MET inhibitors (crizotinib and golvatinib), or by siRNA‐mediated knockdown of HGF or MET, constrained growth of chemoresistant SCLC cells through the inhibition of ERK and AKT signals. Furthermore, treatment with either crizotinib or golvatinib suppressed the systemic metastasis of SBC‐5 cell tumors in natural killer cell‐depleted SCID mice, predominantly through cell cycle arrest. These findings reveal the therapeutic potential of targeting the HGF/MET pathway for inhibition, to constrain tumor progression of SCLC cells showing aberrant activation of HGF/MET signaling. We suggest that it would be clinically valuable to further investigate HGF/MET‐mediated signaling in SCLC cells. Abstract : In the present study, we demonstrated that HGF/MET signaling was aberrantly activated in chemo‐resistant or chemo‐relapsed SCLC cell lines by the secretion of HGF and/or MET copy number gain. Furthermore, the MET inhibitors crizotinib and golvatinib were able to inhibit cell growth, and prevent systemic metastasis of SCLC cells in vivo, predominantly via cell cycle arrest. These findings indicate that inhibition of HGF/MET signaling may constrain tumor progression of SCLC cells exhibiting aberrant activation of the HGF/MET pathway.